Peer Interaction and Akidah Akhlak Instruction as Predictors of Religious Character - Fauziah Qhotrun Nada; Faizatul Widat; Muhyidin; Achmad Mahrus Helmi (Educazione: Journal of Education and Learning, 2025)
This study investigates the influence of peer interaction and Akidah Akhlak education on the religious character of students. With the increasing moral challenges adolescents face in the modern era, understanding the factors contributing to religious identity formation is crucial. Previous research has explored the role of social influences and religious education in shaping students' values. However, few studies have examined the combined impact of peer relationships and Akidah Akhlak subjects. This research uses a quantitative approach, employing a survey method with 60 randomly selected students to assess the effects of peer interaction and Akidah Akhlak education on religiosity. The data were analyzed using multiple linear regression to test the relationship between these variables. The findings reveal that peer interaction and Akidah Akhlak education have a significant positive effect on students' religiosity, with peer interaction showing a more substantial influence. These results highlight the importance of fostering a supportive social environment and integrating effective religious education to strengthen students' religious character. The study's implications suggest that combining social and educational factors can enhance religious development, offering valuable insights for educators and policymakers aiming to promote religious and moral values in schools.